Goat manure waste and palm oil mill effluent, viable crude oil degradation substrates: A thermodynamic and composting investigation studies - Kingsley Amechi Ani; Chinedu Matthew Agu; Esonye Chizoo; Chukwuma Henry Kadurumba; Isiguzo Edwin Ahaneku (Waste Management Bulletin, 2024)
The composting and thermodynamic processes of crude oil (CO) degradation using the compost of goat manure origin (CGMO) and compost of palm oil mill effluent origin (CPOMEO) were studied. Microbial activity was investigated using the carbon dioxide (CO₂) evolution test. The physiochemical properties of the composts and that of the treated CO-contaminated soil (COCS) were also investigated. In particular, CGMO significantly improve CO degradation with the highest CO₂ evolution rate of 45 mg/g compared to the CPOMEO and the control. The CO degradation rates of 85.7 %, 71.4 %, and 14 % corresponded to the first-order CO degradation rate constants of 0.743 day−1, 0.689 day−1, and 0.136 day−1 for CGMO, CPOMEO, and control, respectively. The Fourier transforms infrared (FTIR) spectral pattern for both composts revealed adsorption bands that were identifiable with polysaccharides, potassium, and nitrogen, whereas the scanning electron microscope and energy dispersive spectrophotometry (SEMEDX) of CPOMEO indicated carbon and oxygen as the sole compositions. The negative ΔG and ΔH values indicated the spontaneity and exothermic nature of the CO composting process, respectively.